(-a-2b+5)7ab=

Simple and best practice solution for (-a-2b+5)7ab= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-a-2b+5)7ab= equation:


Simplifying
(-1a + -2b + 5) * 7ab = 0

Reorder the terms:
(5 + -1a + -2b) * 7ab = 0

Reorder the terms for easier multiplication:
7ab(5 + -1a + -2b) = 0
(5 * 7ab + -1a * 7ab + -2b * 7ab) = 0

Reorder the terms:
(35ab + -14ab2 + -7a2b) = 0
(35ab + -14ab2 + -7a2b) = 0

Solving
35ab + -14ab2 + -7a2b = 0

Solving for variable 'a'.

Factor out the Greatest Common Factor (GCF), '7ab'.
7ab(5 + -2b + -1a) = 0

Ignore the factor 7.

Subproblem 1

Set the factor 'ab' equal to zero and attempt to solve: Simplifying ab = 0 Solving ab = 0 Move all terms containing a to the left, all other terms to the right. Simplifying ab = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(5 + -2b + -1a)' equal to zero and attempt to solve: Simplifying 5 + -2b + -1a = 0 Reorder the terms: 5 + -1a + -2b = 0 Solving 5 + -1a + -2b = 0 Move all terms containing a to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -1a + -5 + -2b = 0 + -5 Reorder the terms: 5 + -5 + -1a + -2b = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1a + -2b = 0 + -5 -1a + -2b = 0 + -5 Combine like terms: 0 + -5 = -5 -1a + -2b = -5 Add '2b' to each side of the equation. -1a + -2b + 2b = -5 + 2b Combine like terms: -2b + 2b = 0 -1a + 0 = -5 + 2b -1a = -5 + 2b Divide each side by '-1'. a = 5 + -2b Simplifying a = 5 + -2b

Solution

a = {5 + -2b}

See similar equations:

| -5(x+6)=10 | | 0.5w+5=6 | | 3/5x=7 | | 5.6x-2.4=2.3x+1.5 | | 7-b-4=3b+5 | | -56=-7v | | 4(-3x-y-15)= | | 0.1/1.8 | | 12x^2-40x=0 | | 5y-5-4y=7-4 | | 6a^2-8a= | | (20x^5)/(5x^3) | | 7r^2-32r+16=0 | | 5-5y=4(-y-6)+5(4y+3) | | 4x^3-12x^2-40x=0 | | 20x^5/5x^3 | | -9x(-36)=18 | | a^4-4a^2-6= | | 1/3(w+2)=-5 | | jx+by=c | | 12x-3x+14=8+6+9x | | 9y-4=12y-2 | | 864=(1/2)(18*4)(l)+(18*18) | | 3(-4)+3(-6)=-6 | | 1/3(w+2) | | 3=-1+x | | 8/9x-8=y | | -9(0)-7y=63 | | (5x+2)(10x-3)=(2x+3)(x-8) | | 3(n-11)=42 | | n/4-2/3=5/6 | | 4w-5/3=2w+12/4+w/2 |

Equations solver categories